Factors influencing the willingness to pay for masks during the COVID-19 pandemic: Empirical evidence from Indonesia - Restiatun, Restiatun; Yani, Akhmad; Bariyah, Nurul; Suradi, Romi (Asian Development Policy Review, 2023)
The purpose of this study was to investigate the factors affecting the willingness-to-pay (WTP) value of cloth and disposable masks during the pandemic. Each type of mask has its advantages, and each individual has different considerations when choosing the mask they will buy and use. Primary data were obtained from survey questionnaires, with the qualified participants being income earners. Using a snowball sampling technique, a total of 1144 people were selected as participants from 14 Indonesian provinces. Data collection was carried out and questionnaires were distributed through Google Forms and a WhatsApp group, respectively, for 7 days. The results showed that the WTP value of cloth and disposable masks was significantly influenced by similar variables, including age, education, income level, number of household members, activities outside the home, and the presence of comorbidities. All the variables had similar effects on the WTP value of cloth and disposable masks. The absence of differences in the WTP value implies that the most important consideration in reducing the risk of exposure to Covid-19 was not the type of mask but the discipline of wearing a mask when performing activities outside the home.